Pengaruh Gender Diversity, Millennial Leadership, dan Corporate Social Responsibility terhadap Nilai Perusahaan - Aldesis, Jihan Farrah; Sebrina, Nurzi (Universitas Negeri Padang, 2025)
This study examines the effect of gender diversity, millennial leadership, and corporate social responsibility on firm value. The population is a company listed on the Indonesia Stock Exchange in 2018-2021 which is included in LQ 45. Using purposive sampling, 30 companies were found. Firm value is measured by the Tobin's Q model. Gender diversity is the proportion of women on the board of directors, millennial leadership is the proportion of directors in the age range, and corporate social responsibility (CSR) is based on the Global Reporting Initiative Standard index (GRI Standard) Secondary data obtained from annual Company reports are obtained from the official website of the Indonesia Stock Exchange. Hypothesis testing was carried out by analysis using the panel regression method. The results of this panel show that gender diversity and corporate social responsibility have no effect on firm value, but millennial leadership have effect on firm value. In liquid companies, gender diversity, millennial leaders, and disclosure of corporate social responsibility activities cannot explain changes in firm value.